Formation process and mechanical properties in selective laser melted multi-principal-element alloys. (10th January 2023) - Peng, Jing; Li, Jia; Liu, Bin; Wang, Jian; Chen, Haotian; Feng, Hui; Zeng, Xin; Duan, Heng; Cao, Yuankui; He, Junyang; Liaw, Peter K.; Fang, Qihong
Highlights: Selective laser melted FeCrNi multi-principal-element alloy shows the excellent ultimate tensile strength of ( σ UST = 996 MPa ) and the splendid ductility ( ε = 37 % ). All constituent elements are evenly distributed at micron scale, but Cr element is obviously segregated at atomic scale. Dynamic evolution of microstructure during selective laser melting is revealed by molecular dynamic simulation. A microstructure-based physical model is established to evaluate the contribution of microstructure to strength. Abstract: Additive manufacturing is believed to open up a new era in precise microfabrication, and the dynamic microstructure evolution during the process as well as the experiment-simulation correlated study is conducted on a prototype multi-principal-element alloys FeCrNi fabricated using selective laser melting (SLM). Experimental results reveal that columnar crystals grow across the cladding layers and the dense cellular structures develop in the filled crystal. At the micron scale, all constituent elements are evenly distributed, while at the near-atomic scale, Cr element is obviously segregated. Simulation results at the atomic scale illustrate that i) the solid-liquid interface during the grain growth changes from horizontal to arc due to the radial temperature gradient; ii) the precipitates, microscale voids, and stacking faults also form dynamically as a result of the thermal gradient, leading to the residual stress in the SLMed structure. In addition, we established a microstructure-based physical model based on atomic simulation, which indicates that strong interface strengthening exists in the tensile deformation. The present work provides an atomic-scale understanding of the microstructural evolution in the SLM process through the combination of experiment and simulation.